Identification of a circular intermediate in the transfer and transposition of Tn4555, a mobilizable transposon from Bacteroides spp. - Smith, C. Jeffrey; Parker, Anita C. (East Carolina University, 1993)
Transmissible cefoxitin (FX) resistance in Bacteroides vulgatus CLA341 was associated with the 12.5-kb, mobilizable transposon, Tn4555, which encoded the 13-lactamase gene cfxA. Transfer occurred by a conjugation-like mechanism, was stimulated by growth of donor cells with tetracycline (TC), and required the presence of a Bacteroides chromosomal Tcr element. Transconijugants resistant to either FX, TC, or both drugs were obtained, but only Fx Tcr isolates could act as donors of Fxr in subsequent matings. Transfer of Fxr could be restored in FxF Tc' strains by the introduction of a conjugal Tcr element from Bacteroidesfragilis V479-1. A covalently closed circular DNA form of Tn4555 was observed in donor cells by Southern hybridization, and the levels of this circular transposon increased significantly in cells grown with TC. Both the cfxA gene and the Tn4555 mobilization region hybridized to the circular DNA, suggesting that this was a structurally intact transposon unit. Circular transposon DNA purified by CsCI-ethidium bromide density gradient centrifugation was used to transform Tcs B. fragilis 638, and FXr transformants were obtained. Both the circular form and the integrated Tn4555 were observed in transformants, but the circular form was present at less than one copy per chromosomal equivalent. Examination of genomic DNA from Fxr transformants and transconjugants revealed that Tn4555 could insert at a wide variety of chromosomal sites. Multiple transposon insertions were present in many of the transconjugants, indicating that there was no specific barrier to the introduction of a second transposon copy. Originally published Journal of Bacteriology, Vol. 175, No. 9, May 1993
Keywords: Tn4555; Mobilizable transposon; Circular DNA